2012
DOI: 10.1248/cpb.60.23
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fourteen Alkaloids from Uncaria rhynchophylla Hooks and Leaves Using HPLC-Diode Array Detection-Atmospheric Pressure Chemical Ionization/MS Method

Abstract: The purpose of the study is to compare alkaloid profile of Uncaria rhynchophylla hooks and leaves. Ten oxindole alkaloids and four glycosidic indole alkaloids were identified using HPLC-diode array detection (DAD) or LC-atmospheric pressure chemical ionization (APCI)-MS method, and a HPLC-UV method for simultaneous quantification of major alkaloids was validated. The hooks are characterized by high levels of four oxindole alkaloids rhynchophylline (R), isorhynchophylline (IR), corynoxeine (C) and isocorynoxein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…C, corynoxeine-N-oxide (C-NO), 18,19-dehydrocorynoxinic acid (DCA), 18,19-dehydrocorynoxinic acid B (DCAB), isocorynoxeine-N-oxide (IC-NO), IC, IR and R were isolated from the CHCl 3 extract of U. rhynchophylla [1,8,20] were isolated from the urine of rats administered IC orally [14]. The identification of these compounds was confirmed by spectral analysis including UV, 1D and 2D NMR, mass spectrometry (MS) and circular dichroism experiments (CD).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…C, corynoxeine-N-oxide (C-NO), 18,19-dehydrocorynoxinic acid (DCA), 18,19-dehydrocorynoxinic acid B (DCAB), isocorynoxeine-N-oxide (IC-NO), IC, IR and R were isolated from the CHCl 3 extract of U. rhynchophylla [1,8,20] were isolated from the urine of rats administered IC orally [14]. The identification of these compounds was confirmed by spectral analysis including UV, 1D and 2D NMR, mass spectrometry (MS) and circular dichroism experiments (CD).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…These alkaloids exhibit wide beneficial effects on the cardiovascular and cardiocerebral vascular systems, such as a protective effect on ischemiainduced neuronal damage in the rat hippocampus [4], inhibitory effect on 5-HT 2A receptor function in the mouse brain [5], vasodilator action [6] and antagonist effect on angiotensin II-induced proliferation rat vascular smooth muscle cells [7]. IC is one of the major oxindole alkaloids in herbal medicine [8] and also shows a protective effect on glutamate-induced neuronal damage in cultured cerebellar granule cells from rat [9], the inhibitory activities on the 5-HT 2A receptor in mouse brain [5] and lipopolysaccharide (LPS)-induced NO release in primary cultured rat cortical microglia [10].…”
Section: Introductionmentioning
confidence: 99%
“…RIN, CNX, CNXB were also riched in UMW (0.739-0.857 mg/g for RIN, 0.366-0.394 mg/g for CNX, trace-0.197 mg/g for CNXB) than other four U. species (trace-0.321 mg/g for RIN, trace for CNX, trace for CNXB). Several studies on HPLC analysis of the URM have been reported, [12][13][14] and most of them focused on chemical profiling of alkaloids. However, there were large variations in the content of these bioactive alkaloids in the U. species samples according to the species and different geographic locations, which may be responsible for the different therapeutic efficacies of these herbal plants.…”
Section: Resultsmentioning
confidence: 99%
“…Several holistic chemical profiling methods of the URM have been reported, such as the screening and identification of six oxindole alkaloids and four indole alkaloids in various parts of URM by HPLC, 12) the quantification of ten oxindole alkaloids and four glycosidic alkaloids using HPLC-UV and LC-MS technologies, 13) and the profiling of the alkaloids using HPLC-DAD-quadrupole time-of-flight mass spectrometry (Q-TOF/MS) method. 14) However, in these literature, the identification or quantification of the URCU from other four botanical origins were still not fully understood.…”
mentioning
confidence: 99%
“…1), has been of interest, especially using high-performance liquid chromatography with tandem mass spectrometry (LC-MS). [1][2][3][4][5] The plentiful pharmacological activities and in vivo identification in biosystems of COR have been investigated. [6][7][8][9][10][11][12][13] We have reported that after oral administration, COR was hydroxylated into 11-hydroxycorynoxeine (M1) and 10-hydroxycorynoxeine (M2), which successively glucuronidated into 11-hydroxycorynoxeine 11-O-β-D-glucuronide (M3) and 10-hydroxycorynoxeine 10-O-β-D-glucuronide (M4), respectively.…”
Section: Introductionmentioning
confidence: 99%